2018
DOI: 10.1093/nar/gky1048
|View full text |Cite
|
Sign up to set email alerts
|

BRENDA in 2019: a European ELIXIR core data resource

Abstract: The BRENDA enzyme database (www.brenda-enzymes.org), recently appointed ELIXIR Core Data Resource, is the main enzyme and enzyme-ligand information system. The core database provides a comprehensive overview on enzymes. A collection of 4.3 million data for ∼84 000 enzymes manually evaluated and extracted from ∼140 000 primary literature references is combined with information obtained by text and data mining, data integration and prediction algorithms. Supplements comprise disease-related data, protein sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
324
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(334 citation statements)
references
References 35 publications
10
324
0
Order By: Relevance
“…We therefore applied the protMLP method to Adenosine Kinases (ADK), an extensively studied (Wolf-Watz et al, 2004;Nguyen et al, 2017;Schrank et al, 2009) family that catalyzes the interconversion of adenosine nucleotides. As has been observed in other proteins (Engqvist, 2018), we found that the ADK homologs' temperatures of optimal activity (Nguyen et al, 2017;Jeske et al, 2019) were correlated with measured originating species' growth temperatures (r = 0.79). While there were too few ADK sequences to train an over-determined MLP, a linear regression was already highly accurate at predicting the originating species' growth temperature (RMSE = 3.9 °C, r = 0.86) (Fig.…”
Section: Adenosine Kinases' Biochemical Characteristics Correlate Witsupporting
confidence: 82%
“…We therefore applied the protMLP method to Adenosine Kinases (ADK), an extensively studied (Wolf-Watz et al, 2004;Nguyen et al, 2017;Schrank et al, 2009) family that catalyzes the interconversion of adenosine nucleotides. As has been observed in other proteins (Engqvist, 2018), we found that the ADK homologs' temperatures of optimal activity (Nguyen et al, 2017;Jeske et al, 2019) were correlated with measured originating species' growth temperatures (r = 0.79). While there were too few ADK sequences to train an over-determined MLP, a linear regression was already highly accurate at predicting the originating species' growth temperature (RMSE = 3.9 °C, r = 0.86) (Fig.…”
Section: Adenosine Kinases' Biochemical Characteristics Correlate Witsupporting
confidence: 82%
“…Both reviewed and unreviewed sequences are considered and stored as clustered UniPac sequences (src/uniprot.sh). To increase the sequence pool for a given reaction, alternative EC numbers from BRENDA [37] and from the Enzyme Nomenclature Committee https://www.qmul.ac.uk/sbcs/ iubmb/enzyme/ are integrated (src/altec.R, dat/brenda_ec.csv).…”
Section: Pathway and Sequence Databasesmentioning
confidence: 99%
“…Biotechnology, bioengineering, and the universe of enzymes contain large gold mines for developing and improving existing enzyme functions for applications as well as for discovering enzymes with novel functions. The enzymatic reaction diversity, the molecular elucidation of metabolic pathways, their information retrieval, and advanced bioinformatics tools are growing continuously and will have, undoubtedly, a major influence on the further growth of bioeconomies.…”
Section: New Value Chains and Widening Connections Between Industriesmentioning
confidence: 99%